Maintaining Functional Integrity in Multi-Agent Systems for Resource Allocation - Cetnarowicz, Krzysztof; Dreżewski, Rafał (COMPUTING AND INFORMATICS, 2012)
The resource allocation problem is the problem of assigning resources needed to accomplish some tasks. Such problems are present in many practical domains and are generally very hard to solve. In the paper two multi-agent systems for resource allocation are presented. Each of them uses different mechanisms (based on the ideas of ``free agents’’ and ``life energy’’) for maintaining functional integrity related with the number of agents in the population. The preliminary results of simulation experiments are also presented and the mechanisms of maintaining functional integrity are analyzed.